Drivers to implement the circular economy in born-sustainable business models: a case study in the fashion industry - Ostermann, Cristina M.; Nascimento, Leandro da Silva; Steinbruch, Fernanda Kalil; Callegaro-de-Menezes, Daniela (Revista de gestão, 2021)
PurposeThis study aims to identify the drivers for adopting the circular economy (CE) in a born-sustainable business of the fashion sector.Design/methodology/approachAn exploratory case study was carried out with a unique and relevant case: the only Brazilian company implementing circularity practices defined through a sectoral commitment, the 2020 Circular Fashion System Commitment.FindingsFrom an analysis of the literature, a theoretical scheme composed of internal and external drivers is proposed. In the case studied, there is a prevalence of internal drivers that led the company to implement the CE. Most of the internal drivers described by the literature were identified in this research, except for two: profitability and available technology. Regarding the external drivers, of the 12 listed, only laws and regulations were identified. Thus, the results suggest that internal drivers are more numerous and may be more prominent than external ones for CE adoption in the born-sustainable business.Research limitations/implicationsDue to its exploratory design and unique case study, the research does not allow generalizations, suggesting replication with a larger number of companies and carrying out quantitative research with born-sustainable companies and incumbent companies, for comparison. Considering that there is a difference between companies that decide for sustainable practices and companies that were already born sustainable, it can be questioned if the drivers for implementing CE for both companies are also different.Originality/valueThis study proposes a theoretical scheme that indicates the main internal and external drivers for companies' CE implementation. Developed from a literature review and applied in an empirical case, this scheme is comprehensive and can be adopted to analyze companies of different sizes and industries. Hence, this paper generates new perspectives for CE literature.